Social deixis in speech of Bahdinan area according to Fillmore Model - Ali, Sherzad S. (Humanities Journal of University of Zakho, 2019)
Social deixis concerns social relationships between participants, their status and relations to the topic of discourse .The present research aims at investigating the use of Social deixis in speech of Bahdinan area according to (Fillmore 1975: 39) Model. The research entitled “Social deixis in Speech of Bahdinan area “tries to explain the notion of Social deixis, its fields, and how to study it pragmatically.The research consists of two chapters. The first one is “Deixis and Social deixis” and it deals with the idea, characteristics, types and relationships of Social deixis. The second one is “ Deixis and fields of Social deixis “ and it deals with the Deictic items and fields of Social deixis according to Fillmore( 1975)and this model connects the Social deixis with appreciation expressions , honorifics, nicknames , kinship terms, and personal pronouns.